2017
DOI: 10.1177/1753193416686884
|View full text |Cite
|
Sign up to set email alerts
|

Super Kutler flap: an alternative technique for reconstruction of fingertip defects

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Night extension splinting can be used to try and counteract any flexion contractures that may develop. 3,12 Hook nail deformities may occur when the distal margin of the flap is inset too tightly, sewn into the nail matrix, or the pulp is reconstructed without adequate nail matrix. 50 Although numerous studies noted an incidence of the complication (25 cases in total), it was rarely identified as a concerning issue to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Night extension splinting can be used to try and counteract any flexion contractures that may develop. 3,12 Hook nail deformities may occur when the distal margin of the flap is inset too tightly, sewn into the nail matrix, or the pulp is reconstructed without adequate nail matrix. 50 Although numerous studies noted an incidence of the complication (25 cases in total), it was rarely identified as a concerning issue to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Night extension splinting can be used to try and counteract any flexion contractures that may develop. 3,12…”
Section: Discussionmentioning
confidence: 99%
“…The one most commonly used is an advancement flap designed on one or two digital arteries and the digital nerves, such as Segmuller, extended Segmuller, Mouchet-Gilbert, and Venkataswami flaps (Adani et al., 1997; Tang et al., 2014). These flaps cover an area larger than the Atasoy and Kulter flaps and their variants (Arpaci et al., 2017; Tang et al., 2014) and are more useful for defects larger than 1–1.5 cm. These flaps are an extension of the Atasoy flap (a local V-Y advancement flap, covering a defect of or around 1 cm); they are designed for a larger tissue defect.…”
Section: The Commonly Used Flaps For a Distal Defect Of A Moderate Sizementioning
confidence: 99%
“…Functionally a flap transfer without sensation is not as good as conservative treatment with moist antiseptic dressings. Sensate flaps are preferred in fingertip or thumb tips when flaps are used (Adani and Woo, 2017; Arpaci et al., 2017; Tang et al., 2014; Vitse et al., 2017). However, harvesting a flap would always cause donor site damage.…”
Section: Future Perspectivesmentioning
confidence: 99%